Аналіз еволюції та сучасного стану банківської системи України - Аборчі, О.В. (Стратегія і механізми регулювання промислового розвитку, 2013)
Проведено аналіз еволюції та сучасного стану структури банківської системи України. Досліджено витоки національної банківської системи, наведено авторський варіант періодизації її розвитку з виділенням найбільш значущих подій, а також подано їх коротку оцінку. Зроблено висновок про те, що національна банківська система України пройшла 7 основних етапів розвитку, перший з яких припадає на радянський період. На кожному етапі в банківській системі відбувалися якісні та кількісні трансформації, які в результаті привели до формування стійкого ядра системоутворюючих банків, здатних протистояти циклічним коливанням і у яких сконцентровано більшу частину активів і зобов'язань. Проводится анализ эволюции и современного состояния структуры банковской системы Украины. Исследуются истоки национальной банковской системы, приводится авторский вариант периодизации её развития с выделением наиболее значимых событий, а также даётся их краткая оценка. Сделан вывод о том, что национальная банковская система Украины прошла 7 основных этапов развития, первый из которых приходится на советский период. На каждом этапе в банковской системе происходили качественные и количественные трансформации, которые в итоге привели к формированию устойчивого ядра системообразующих банков, способных противостоять циклическим колебаниям и сконцентрировавших большую часть активов и обязательств. The article analyzes the evolution and current state of the structure of Ukraine’s banking system. It is shown that in a short period of time (20 years), the national banking system has gone through seven main stages, turning from a mass of banks formed spontaneously to an orderly and regulated link in the economic system. At each stage, the banking system of Ukraine experienced serious quantitative and qualitative transformations that ultimately helped to create a strong core of banks able to withstand cyclical fluctuations and which concentrate a large part of the assets and liabilities. In the first 4 phases (1987-2000), there occurred the formation of the foundations for the banking system in order to implement the necessary reforms, and the key legislation was adopted that allowed at the beginning of the XXI century to form the main vectors of development for the future. In the 2001-2008, there was actually the peak of the Ukrainian banking sector, which is characterized by a significant expansion of the range of banking services and branch network, a substantial increase in capital and assets of banks, high positive dynamics of changes in key indicators of their activities, large-scale presence of foreign participants, the emergence of large private important banks, and so on. The crisis of 2008-2009 has led to significant changes in the banking system, which is reflected in its slower development, the fall of the key indicators, the reduction of the branch network of banks and the nationalization of some of them. At the present stage,the Ukrainian banking system is still feeling the effects of the crisis, and in fact it is still at the stage of post-crisis recovery.